An Analysis and Evaluation of Student Nurses’ Participation in Ethical Decision Making - Han, Sung-Suk; Ahn, Sung-Hee (2000)
This study analyses the types and frequencies of ethical dilemmas and the rationale of ethical decision making in student nurses; it also evaluates their decision making. One hundred senior student nurses who were enrolled in a two-credit course in nursing ethics were asked to provide an informal description of a dilemma that they had experienced during their clinical practice. The results were as follows. The ethical dilemmas identified fell into four categories and were of 27 types. Those most frequently experienced were ‘family giving up on a patient because he or she could not be cured’, and ‘not telling the truth to the patient’. The Korean Nurses’ Code of Ethics was applied, in particular the preamble, and the third, fourth, seventh and tenth clauses. The most common rule of ethics and principle applied in these nurses’ ethical decision making were veracity and nonmaleficence. With regard to the moral reasoning process, the primary concern was the welfare of the patients. These students were equipped with the ability to exercise critical and reflective thought when they experienced ethical dilemmas.
Keywords: Ethical Dilemma; Ethical decision making